Engaging New Yorkers in Discussion Around Segregated Health Care: The Health Equity and Access to Care (HEAC) Project - Diana Romero; Samantha Weckesser; Jenai Jackson; Adeola Ayedun; Duncan Maru (Journal of Participatory Research Methods)
The *Health Equity and Access to Care* (HEAC) project was a community-engaged research project that involved focus groups (n=35) and key informant interviews (n=9) designed to examine healthcare segregation in New York City (NYC). The project utilized a multi-faceted community-engaged approach that involved stakeholders from four different sectors (municipal institutions, civil society groups, academic/research and business entities) to recruit a diverse, broad-based sample of New Yorkers who accessed care within a year of participating in the study. We employed a phased information dissemination and outreach strategy allowing for a wide range of ways that community members from different groups could contribute to the project, through both recruitment and participation. In this report we demonstrate our broad conceptualization of "community" and the specific means for implementing a community-engaged project on health equity to ensure participation by a diverse sample. We describe successes and challenges confronted in generating a sample of participants who could contribute insights and experiences related to access to care in a segregated healthcare system.